Poverty Persistence and Transitions in Uganda : A Combined Qualitative and Quantitative Analysis. - Lawson, D; McKay, A; Okidi, J (GPRG, 2004)
Despite Uganda’s impressive reduction in monetary based poverty, during the 1990’s, recent evidence has shown there to be substantial mobility into and out of poverty. This paper represents on the first attempts to combine both qualitative and quantitative information to understand the factors underlying such poverty transitions and persistence. Using national participatory assessments and panel data we find a number of factors, such as lack of key physical assets, high dependency ratios and increased household size are identified by both qualitative and quantitative approaches as being major drivers of poverty dynamics. The paper also demonstrates that there is considerable value added in combining the two approaches allowing us to provide a much richer understanding of many of the processes underlying poverty and poverty transitions.